ANALISIS KONFLIK MANUSIA DENGAN GAJAH DI SEKITAR RESORT PEMERIHAN TAMAN NASIONAL BUKIT BARISAN SELATAN BERDASARKAN PERSEPSI MASYARAKAT KECAMATAN BENGKUNAT KABUPATEN PESISIR BARAT - Popy Pratiwi; Dian Iswandaru; Rudi Hilmanto; Indra Gumay Febryano; Ismanto Ismanto; Tri Sugiharti; Subki Subki (Jurnal Belantara, 2022)
Human-elephant conflict occurs due to the release of elephants from forest areas and into human settlements so that there is no balance between human and elephant welfare. This research was conducted to determine how people's perceptions of human-elephant conflict that occurred around the Bukit Barisan Selatan National Park forest area during October 2020-November 2020. Structured interviews were collected for data collection, 45 respondents were selected by purposive sampling based on the slovin formula. Data analysis was performed using a Likert scale. The results showed that most of the community agreed with the indicator if human-elephant conflict was detrimental to humans (4.75) and reduced the community's economy (4.6). The conflict between humans and elephants creates negative perceptions of the community towards elephants, which are animals that eat and destroy plants. However, the community still has an awareness of the preservation of elephants so that they have a positive perception of elephants in the form of animals that need to be protected and can be used as tourist objects. The community will carry out a blockade and blockade if the elephants will enter the residential area to suppress the amount of conflict that occurs..